2020
DOI: 10.1159/000507080
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model of Balloon Angioplasty Injury in Rat Arteriovenous Fistula

Abstract: Background: There are very few animal models of balloon angioplasty injury in arteriovenous fistula (AVF), hindering insight into the pathophysiologic processes following angioplasty in AVF. The objective of the study was to develop and characterize a rat model of AVF angioplasty injury. Methods: Balloon angioplasty in 12-to 16-week-old Sprague-Dawley rats was performed at the arteriovenous anastomosis 14 days post-AVF creation with a 2F Fogarty balloon catheter. Morphometry and protein expression of endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Many clinical studies have shown that the most common causes for hospitalization of these patients are cardiovascular and cerebrovascular diseases, infections and access complications. 25,26 In the current study, the hospitalization rate of patients with AVF was lower than that of patients with CVC (P<0.05), suggesting that patients undergoing MHD with CVC might have a poor prognosis. Our results are consistent with Almasri et al 27 It is plausible that despite optimized biocompatibility, the catheter still carries a high risk of infection and access related complications as a central venous foreign body.…”
Section: Discussionmentioning
confidence: 50%
“…Many clinical studies have shown that the most common causes for hospitalization of these patients are cardiovascular and cerebrovascular diseases, infections and access complications. 25,26 In the current study, the hospitalization rate of patients with AVF was lower than that of patients with CVC (P<0.05), suggesting that patients undergoing MHD with CVC might have a poor prognosis. Our results are consistent with Almasri et al 27 It is plausible that despite optimized biocompatibility, the catheter still carries a high risk of infection and access related complications as a central venous foreign body.…”
Section: Discussionmentioning
confidence: 50%
“…The end of the FV was sutured to the side of the FA to form a femoral fistula, with an anastomotic length of approximately 2.5 mm. The suture was more consistent in structure than that used in human AVF (64,89). In a study by Langer, the average operation time was reduced to 27 min, all 15 rats survived, and the fistula patency rate was 93% at 12 weeks (17,53).…”
Section: Femoral Fistulamentioning
confidence: 97%
“…Both CO and bilirubin produced by HO-1 activity in the cells of cardiovascular tissue ameliorate a diverse range of cardiovascular pathologies due to the effect of these two degradation products on vascular tone [ 163 , 164 ]—along with the stabilization of K + and Na + ion membrane distribution [ 165 ]. Moreover, the regulatory effects of HO-1-generated bilirubin on the expression of ROS by NADPH oxidase has also been demonstrated to be cardioprotective as evidenced by the prolonged survival of mouse-to-rat cardiac xenografts, the inhibition of IR and balloon injury, and improved cardiac functions [ 163 , 166 , 167 ].…”
Section: Heme Oxygenase In Cardiovascular Disease: Limits Of Clinical...mentioning
confidence: 99%